BANDED IRON FORMATIONS AND PALAEOENVIRONMENT: A PROBLEM IN PETROGENESIS - Page D. (My University, 2001)
The mineralogy, chemistry and stratigraphy of Precambrian banded iron formations have been extensively documented, yet the way such formations are produced remains a subject for debate. Differentiation by varving, microbial precipitation and secondary alteration are all seen as possible mechanisms, but discussion returns to the lack of any modern analogue. Nothing like banded iron forms anywhere in the world today or has done during the entire Phanerozoic. Where do we begin with such enigmatic rocks?
Keywords: Precambrian; Докембрий; Precambrian